Community Service to Enhance Educational Skills in Rural Communities - Muh Barid Nizarudin Wajdi; Brata, Diah Puji Nali; Ulya, Fahimatul; Musnaini, Musnaini; Lee, William (STAI Miftahul ULa Nganjuk, 2025)
The Integrated Competency-Based Community Service Program (KPM-IK) in Sidoharjo Village focuses on improving educational skills among local educators and community members. The main objective of this program is to enhance the quality of education by providing relevant training in teaching skills and curriculum development, tailored to local needs. The program employs Participatory Action Research (PAR) as its approach, where students collaborate with the community to identify educational challenges, design training modules, and implement solutions. This method ensures active community participation in the process. Results indicate a significant improvement in teaching skills, with participants showing enhanced abilities in class management, effective teaching methods, and the integration of technology in education. The program has successfully empowered the local community to contribute to sustainable improvements in education, fostering a more effective learning environment in Sidoharjo.